Evaluation of the Management of Gastroschisis in Aristide Le Dantec University Hospital Center in Dakar: A Cross Sectional Study - Souleymane Camara; Daniel Yonga Tenfa; S. Y. Fatou; Fall Yacine; Mbaye Fall; Oumar Ndour (Wolters Kluwer Medknow Publications, 2024)
Introduction: The management of gastroschisis remains problematic in low- and middle-income countries with high perioperative mortality. The objective of this work was to make an initial assessment of our management of gastroschisis. Materials and Methods: This was a monocentric and cross-sectional study including all newborns with gastroschisis between January 2017 and December 2021 in the Pediatric Surgery and Anesthesia Resuscitation Department of the Aristide Le Dantec University Hospital Center from Dakar. The socio-demographic, diagnostic, therapeutic and evolutionary parameters were studied. Results: Eighteen cases of gastroschisis (11 males and 7 females). The mothers' mean age were 23.1 ± 5.7 years old. Only one antenatal diagnosis was made. The mean gestation age were 36.5 ± 1.5 weeks. On admission, the mean age was 16.8 ± 6.3 h and the mean weight 2244 ± 260.3 g. Gastroschisis was complex in four patients. Primary bowel reintegration was performed in 8 cases (44.4%) and progressive reintegration using an Applied Alexis retractor in 9 newborns (55.6%). Main complications were respiratory distress (28.3%) and sepsis (22.2%). The mean duration of return of oral feeding was 5.1 ± 1.9 days. Mortality was 94.4% (17/18). Conclusion: Reducing gastroschisis-related mortality in our low-income countries remains a major challenge.